2020
DOI: 10.1108/jhrm-10-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Marketing in the late Soviet garment industry

Abstract: Purpose This paper aims to study the Soviet state-owned enterprises that were producing ready to wear clothes, engaged in activities that are traditionally associated with “capitalist” marketing and public relations. Particularly, they responded to consumer complaints, monitored customer satisfaction and changed their product features and offer in response to customer feedback. This claim is illustrated using the example of the garment industry in the city Perm. Design/methodology/approach The data comes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…First, our research has identified two simultaneous lines of actions, framing and settlement, through which the governance unit was able to exploit its social skills to induce other actors to cooperate in the refashioning of the field and in accepting the new cultural order based on wine. In this capacity, the case of Operation Vin shares some important similarities with previous studies illustrating the existence of a marketing system in fields traditionally dominated by the direct intervention of the state (Tadajewski and Stole, 2016; Papushina, 2020) or in which the state has adopted marketing practices to stimulate consumption (e.g. Minowa and Witkowski, 2009; Carpenter and Luciano, 2021).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…First, our research has identified two simultaneous lines of actions, framing and settlement, through which the governance unit was able to exploit its social skills to induce other actors to cooperate in the refashioning of the field and in accepting the new cultural order based on wine. In this capacity, the case of Operation Vin shares some important similarities with previous studies illustrating the existence of a marketing system in fields traditionally dominated by the direct intervention of the state (Tadajewski and Stole, 2016; Papushina, 2020) or in which the state has adopted marketing practices to stimulate consumption (e.g. Minowa and Witkowski, 2009; Carpenter and Luciano, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…In the ancient era, it is well documented that the state played a primary role in fostering consumerism by building infrastructure to promote domestic demand for products (Minowa and Witkowski, 2009) or leisure activities (Karababa and Ger, 2011). Other studies have focused on totalitarian regimes, such as the Soviet Union, to illustrate the emergence of a marketing system to direct consumption for ideological purposes (Tadajewski and Stole, 2016; Papushina, 2020; Dufek, 2021). During other historical periods, the state may be driven by forces of globalization to embrace marketing practices to meet consumer culture preferences (Carpenter and Luciano, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Marketing research has indeed amassed a wealth of knowledge regarding consumer behavior, the effectiveness of communication techniques, logistical flows, distribution networks, and the workings of the commercial world. Numerous studies have allowed us to critically assess past state-led planning experiences (Gao, 2018; Papushina, 2020). This knowledge could be mobilized to conceptualize and highlight sustainable alternatives to the current economic order.…”
Section: Research Agenda: How To Market For a Better World?mentioning
confidence: 99%
“…La recherche en marketing a en effet accumulé d’immenses connaissances sur le comportement des consommateurs, l’efficacité des techniques de communication, les flux logistiques, les réseaux de distribution et le fonctionnement du monde commercial. De nombreuses études également ont permis d’évaluer de manière critique les expériences passées de planification dirigée par l’Etat (Gao, 2018 ; Papushina, 2020). Ces connaissances pourraient être mobilisées pour conceptualiser et mettre en évidence des alternatives durables à l’ordre économique actuel, ce qui suppose aussi de repenser le marketing en dehors des cadres du libre marché et de l’économie capitaliste, en délaissant la perspective gestionnaire pour l’orientation politique et l’action publique.…”
Section: Programme De Recherche : Quel Marketing Pour Un Monde Meille...unclassified